Non-pharmacological Treatment for Elderly Individuals With Insomnia: A Systematic Review and Network Meta-Analysis - Kwon, Chan-Young; Lee, Boram; Cheong, Moon Joo; Kim, Tae-Hun; Jang, Bo-Hyoung; Chung, Sun Yong; Kim, Jong Woo (Frontiers in Psychiatry, 2021)
Background: Insomnia causes a huge socioeconomic burden among the elderly, and is not simply a health problem. This study aimed to determine the comparative advantage of the effectiveness and acceptability of non-pharmacological interventions available for elderly individuals with insomnia. Methods: Comprehensive searches in 13 medical databases were performed to find relevant randomized controlled trials (RCTs) up to August 2019. Two independent reviewers performed study selection, data extraction, and quality assessment of included RCTs using the Cochrane Collaboration's risk of bias. A network meta-analysis within the frequentist model was performed by combining direct and indirect evidence from all available RCTs. The primary outcomes were effectiveness as measured by the Pittsburgh Sleep Quality Index (PSQI) total score and acceptability by the incidence of all-cause drop-out. Results: Twenty-eight RCTs involving 2,391 participants were included. Compared to wait-list, acupuncture (standardized mean difference −4.37, 95% confidence interval −8.53 to −0.12), acupuncture combined with benzodiazepines (−5.20, −9.82 to −0.57), behavioral therapy (−10.44, −17.31 to −3.58), benzodiazepines (−4.28, −8.45 to −0.11), benzodiazepines combined with cognitive behavioral therapy (CBT) (−7.18, −12.17 to −2.19), and CBT (−4.93, −8.63 to −1.22) showed significant superiority in their effectiveness. No significant comparative superiority or inferiority was found in terms of acceptability. Conclusions: In terms of effectiveness as indicated by the PSQI total score, compared to wait-list, superior benefits were observed for acupuncture, acupuncture combined with benzodiazepines, behavioral treatment, benzodiazepines, benzodiazepines combined with CBT, and CBT. Importantly, combined treatments, including benzodiazepines combined with CBT or with acupuncture, were generally superior to other monotherapies. In terms of acceptability, there was not enough data to draw conclusions. However, most RCTs included had methodological problems related to the lack of blinding procedure, suggesting a risk of effect size overestimation. Registration: CRD42019145518.